PEMANFAATAN RESIDU KOMPOS TKKS DENGAN NPK MAJEMUK SETELAH PENANAMAN JAGUNG MANIS UNTUK TANAMAN KEDELAI EDAMAME - Asih Lestari; Murniati '; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research aims to find out the effect of palm oil fruit bunch compost with NPK complex’s residues after sweet corn planting for edamame soybean’s growth and production and to find out the dose of residual from palm oil fruit bunch compost with NPK complex in sweet corn planting which utilize to edamame soybean. The research was conducted at the experimental farm of the Agriculture Faculty, University of Riau in June to August 2014. The experiment was arranged in completely randomized design (CRD) with eight treatments and three replications. The data obtained were analyzed statiscally using analyze of variance and tested further by Duncan multiple range test at 5% level. The result showed that palm oil empty fruit bunch compost with NPK complex’s residue after sweet corn planting significantly effect to number of pods per plot and fresh pod weight per plot, but had no significant effect to plant height, the number of branches per plant, number of filled pods per plant and filled pods percentage. The residual of 5 ton palm oil fruit bunch compost with 150 kg NPK complex/ha from sweet corn planting is utilize to edamame soybean.   Keywords : Residue, palm oil fruit bunch compost with NPK complex, edamame soybean.